Power quality analysis for the distribution systems with a wind power generation system. (August 2016) - Hsu, Cheng-Ting; Korimara, Roman; Cheng, Tsun-Jen
Abstract: This paper investigates the impacts of a large wind power generation system (WPGS) on the distribution system. The installation of various types of distributed generators (DGs) on the distribution system will significantly affect the operating, planning and maintaining strategies of the utility. In this paper, one practical distribution system of Taiwan Power Company (Taipower) is selected for study. Various power quality issues like steady state voltage variation ratio, reverse power, flicker, short-circuit current as well as harmonic are investigated and calculated by applying the computer program simulation and the simplified calculation methods suggested by the International Electrotechnical Commission (IEC). The results will be compared with the Taipower relative standards to demonstrate the feasibility of the WPGS to be installed in the distribution feeder.